MENUMBUHKAN LITERASI NUMERASI MELALUI MODEL PROBLEM BASED LEARNING DITINJAU DARI SELFCONFIDIENCE - Arfandi, Naufal; Wakhyudin, Husni; Listyarini, Ikha; Sulistiyaningsih, Hermien (Universitas Negeri Medan, 2024)
Abstract: The research aims to describe the results of the growth in numeracy literacy of class V students at Siwalan Sawangan Elementary School. The method used in this research is a qualitative method with a case study approach. The data collection techniques used were tests and interviews. The data analysis technique used is according to Mc Tiggret, namely data triangulation. The results of this research show that the participants' good level of self-confidence after implementing the problem-based learning model was able to grow the numeracy literacy of class V students at Siwalan Sawangan Elementary School. Keywords: literacy, confidence, PBL Abstrak: Tujuan penelitian yaitu mendeskripsikan hasil pertumbuhan literasi numerasi peserta didik kelas V SD Negeri Siwalan Sawangan. Metode yang digunakan dalam penelitian ini adalah metode kaulitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah tes dan wawancara. Teknik analisis data yang digunakan adalah menurut Mc Tiggret yaitu triangulasi data. Hasil dari penelitian ini adalah dengan tingkat self confidence yang baik setelah implementasi model problem based learning mampu menumbuh literasi numerasi peserta didik kelas V di SD Negeri Siwalan Sawangan.Kata Kunci: literasi, kepercayaan, PBL